A Measurement Model of Successful Muslim Entrepreneur - Efri Syamsul Bahri; Jauhar Ali; Mohd Mizan Mohammad Aslam (International Journal of Islamic Business and Economics (IJIBEC), 2021)
Approximately 1.4 billion of the world's population lives on less than USD 1 per day, and since 50% of the poorest people are in Muslim countries, the solution is to increase successful Muslim entrepreneurs. Hence, this study aims to create a conceptual model through a literature review and descriptive-qualitative approach. These were employed to determine the indicators of successful Muslim entrepreneurs and the expected factors required to provide a positive and significant effect. Meanwhile, four factors and indicators, each considered to influence successful Muslim entrepreneurs, were identified. Subsequently, the results obtained were conceptual papers and hypotheses that required testing to ensure correctness. It was also used to produce new constructs validated for the individuals and communities of Muslim entrepreneurs. Therefore, this conceptual model is hoped to motivate new, future research and has also been enhanced as a pioneer that has attempted to construct a model for successful Muslim entrepreneurs. Finally, a conceptual model was created, which is the initial contribution to solving poverty among the Muslim population in the world..